Identification of financial factors in economic fluctuations - Francesco Furlanetto; Francesco Ravazzolo; Samad Sarferaz (ETH Zurich, KOF Swiss Economic Institute, 2014)
We estimate demand, supply, monetary, investment and financial shocks in a VAR identified with a minimum set of sign restrictions on US data. We find that financial shocks are major drivers of fluctuations in output, stock prices and investment but have a limited effect on inflation. In a second step we disentangle shocks originating in the housing sector, shocks originating in credit markets and uncertainty shocks. In the extended set-up financial shocks are even more important and a leading role is played by housing shocks that have large and persistent effects on output.
Keywords: C11; C32; E32; 330; VAR; sign restrictions; financial shocks; external finance premium; housing; uncertainty